Perception of incest and effects of reality therapy and psychospirituality programs on the self-esteem and spiritual well-being of adolescent survivors of incest - Rojo-Gigantone, Myrna G. (2003)
This study explored the perceptions of incest trauma and the self and the effects of Reality Therapy and Psychospirituality programs on self-esteem and spiritual well-being of female adolescent survivors were randomly assigned to Reality therapy, Psychospirituality, and Wait-List control groups. Treatment groups received five consecutive daily sessions that lasted from one-and-a-half to two hours. The self-esteem Inventory (SEI) and Spiritual Well-Being Scale (SWBS) data were subjected to ANOVA and Scheffe test at p < .05. Results showed that perceptions of incest trauma centered on betrayal, powerlessness, stigmatization, and traumatic sexualization. Self-perceptions were negative and distorted and desires focused on reuniting with the family. Perceived programs gains complemented the findings on Self-Esteem and Spiritual Well-Being. The findings within groups revealed that both treatment programs effectively enhanced self-esteem and spiritual and existential well-being whereas Psychospirituality did not. The control group had no change. Across groups, results showed no significant change in self-esteem and spiritual well-being.
Keywords: Incest victims; Reality therapy